Vaccination of cattle with TickGARD induces cross-reactive antibodies binding to conserved linear peptides of Bm86 homologues in Boophilus decoloratus - Odongo, D.; Kamau, L.; Skilton, Robert A.; Mwaura, S.; Nitsch, C.; Musoke, A.J.; Taracha, E.A.; Daubenberger, C.A.; Bishop, Richard P. (Elsevier, 2007)
Vaccines based on recombinant Bm86 gut antigen from Boophilus microplus are a useful component of integrated control strategies against B. microplus infestations of cattle. The capacity of such vaccines to control heterologous infestations by two African tick species was investigated. The mean weight of engorged female ticks and mean egg mass per tick were significantly reduced in B. decoloratus infestations, but there was no effect of the vaccine against adult Rhipicephalus appendiculatus. We cloned, sequenced and expressed two Bm86 homologues (Bd86) from B. decoloratus. Amino acid sequence identity between Bd86 homologues (Bd86-1 and Bd86-2) and Bm86 was 86% and 85%, respectively, compared to 93% identity between the variants. Native Bd86 protein in B. decoloratus tick mid-gut sections and recombinant Bd86-1 reacted strongly with sera from TickGARD vaccinated cattle. TickGARD can therefore protect against a heterologous tick species with multiple antigen sequences. Epitope mapping using sera from TickGARD-vaccinated cattle identified two linear peptides conserved between the Bd86 homologues and Bm86. These epitopes represent candidate synthetic peptide vaccines for control of Boophilus spp. and the pathogens transmitted by these tick vectors.